Digital image analysis used to estimate soil moisture / Muhamad Hasrol Rizan - Rizan, Muhamad Hasrol (Faculty of Plantation and Agrotechnology, 2018)
Soil moisture is the assessment of the amount of water in liquid or gaseous state, present in the soil porous space at a given time. Soil moisture directly influences the yield of a crop because it is related to important hydrological processes such as infiltration rate, surface runoff and evapotranspiration. For different water contents, the electromagnetic energy reflected by the soil surface is viewed as different tones of a color space. The digital camera will extract these different tones of a color space to the Red, Green and Blue band. The purpose of this study was to analyse the relationship between the soil moisture and the digital image response of the soil. Samples with different series and depth level were prepared and photographed. The photographs were taken under homogenous light condition. The images were processed for extraction of the mean values in the Red, Green and Blue bands of the RGB colour space. The moisture of the samples was determined with the gravimetric moisture (U(%)). It was observed that the darkening of the soil will increase with the increment of the moisture. For general spectral characteristic, the soils reflected more the red band, followed by green and blue. The result collected using digital image processing shows that mean of RGB colour space relates to the soil moisture. Results from statistical analysis showed that Red band with -0.068 is the nearest negatively correlated to the soil moisture content. As the recommendation upon the result obtained from the experiment, increasing the number of soil sample for an area and compaction of the soil sample during photographed to minimize the effect of shading by the edge of container in order to improve result that will be obtain in future.